Perancangan User Experience Sistem Informasi Klinik berbasis Aplikasi Mobile menggunakan Pendekatan Design Thinking (Studi Kasus: Klinik Dr. Maya) - Gema Isya Luthfi Prathama; Lutfi Fanani; Komang Candra Brata (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
Dr. Maya Clinic has limitations in implementing the E-Health service system; the implementation of E-Health at the clinic is still offline and manual. so that the quality of services provided is not optimal, such as the accumulation of patients in the queue so that the waiting time is too long, and besides that, the administration process is still inefficient. Stakeholders strive to improve the quality of clinical services, namely by implementing mHealth. In developing mHealth, developers need a Dr. Maya Clinic mHealth solution design and a tested high-fidelity prototype. To get satisfactory user experience results, this design integrates user experience (UX) with the design process using the Design Thinking approach. As for the test, it used a user experience questionnaire (UEQ), which was given to 20 evaluator respondents, with 50% coming from Dr. Clinic Maya and 50% from general respondents. The results of the UEQ test obtained an average value scale with a score for each group of assessment items. Attractiveness scored 2,233 points, perspicuity scored 2,125 points, efficiency scored 2,250 points, dependability scored 2,163 points, stimulation scored 2,088 points, and novelty scored 1,838 points. So that the Benchmark UEQ Scales on all assessment group items get Excellent results.